Anesthesia in a patient with Pompe disease: Case report and literature review (Research, Society and Development, 2024)
Pompe disease is a rare autosomal recessive disease. It is an inborn error of metabolism, resulting from a deficiency of the acid alpha-glucosidase enzyme, which results in intralysosomal accumulation of glycogen, clinically manifested by progressive muscle weakness. The aim of this study was to report a case of anesthesia in patient with Pompe disease and review the literature.  Man 47 years old,  who underwent laparoscopic cholecystectomy under total intravenous anesthesia. In the pre-anesthetic evaluation, he presented reduced auscultation in the lung bases, oxygen saturation 96%, atelectasis in right lung, PaO2 74 mmHg and PaCO2 41 mmHg, and severe mixed ventilatory disorder with forced vital capacity 41% of predicted, ARISCAT score of 31 points. Intraoperatively, in addition to routine monitoring, neuromuscular blockade and brain activity and anesthetic depth were monitored. At the end of surgery, the patient was extubated with 100% TOF reversed and administration of sugammadex. BIPAP was installed and sent to the intensive care unit. He evolved without showing clinical signs of respiratory failure and was discharged from hospital without complications. In review, we described 10 cases of patients who underwent surgery, six of them under general anesthesia: 8/10 women, aged 5 months to 56 years.  All with impairment of two or more systems: 5/10 of the cardiovascular system, 8/10 of the respiratory system and 7/10 generalized muscle weakness. These patients require preoperative preparation involving a multidisciplinary team. Anesthesia planning, monitoring and safe reversal of neuromuscular blockade associated with perioperative care are essential for quality and safe care.